2014
DOI: 10.1007/s11356-014-3397-3
|View full text |Cite
|
Sign up to set email alerts
|

A multi-residue method for determination of 70 organic micropollutants in surface waters by solid-phase extraction followed by gas chromatography coupled to tandem mass spectrometry

Abstract: A multi-residue method, based on gas chromatography coupled to tandem mass spectrometry (GC-MS/MS), has been developed for the determination of 70 organic micropollutants from various chemical classes (organochlorinated, organophosphorous, triazines, carbamate and urea, polycyclic aromatic hydrocarbons, polychlorinated biphenyls, pharmaceuticals, phenols, etc.) in surface waters. A single-step SPE extraction using OASIS HLB cartridges was employed for the recovery of target micropollutants. The method has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 49 publications
0
8
0
3
Order By: Relevance
“…Lindane has been detected in the rivers Axios, Evros and Ardas in Greece in similar concentrations in the past years and its presence was attributed to transboundary pollution (Vryzas et al, 2009). In more recent studies, lindane was either not detected (Terzopoulou et al, 2015) or detected up to 0.062 μg/L in Strymon River, Greece (Litskas et al, 2012).…”
Section: Rivers and Drainage Canalsmentioning
confidence: 86%
“…Lindane has been detected in the rivers Axios, Evros and Ardas in Greece in similar concentrations in the past years and its presence was attributed to transboundary pollution (Vryzas et al, 2009). In more recent studies, lindane was either not detected (Terzopoulou et al, 2015) or detected up to 0.062 μg/L in Strymon River, Greece (Litskas et al, 2012).…”
Section: Rivers and Drainage Canalsmentioning
confidence: 86%
“…ALA and possible metabolites such as 2‐chloro‐ N ‐(2,6‐diethylphenyl) acetamide (CDA), 2,6‐diethylaniline (DEA), and 2‐ethyl‐6‐(1‐hydroxyethyl) aniline (HEEA; Figure 1), which can diffuse into groundwater and disperse in the environment, cause serious ecological and physiological problems [20–22]. GC techniques have been considered for multiresidue monitoring methodology of herbicides [23–27]. On the other hand, recent studies showed that LC–MS or tandem mass spectrometry (LC–MS/MS) was used for the determination of ALA and its metabolites [10,28–31].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid chromatography-tandem mass spectrometry (LC-MS/MS), which has the advantages of unambiguous identification and accurate quantification, is the preferred strategy to detect MALs in water [ 10 , 11 , 12 ]. Besides, a pre-concentration step such as solid-phase extraction (SPE) or lyophilization is indispensable for the analysis of water samples [ 13 , 14 , 15 ]. However, the lyophilization procedure is time-consuming (more than 24 h for lyophilization) and the quantification of target compounds would be affected by the impurities.…”
Section: Introductionmentioning
confidence: 99%